PANDANGAN ULAMA’ FIQIH TERHADAP ADAT PANCER DALAM PERNIKAHAN - Muhammad Jufri; Ahmad Ghozali (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
The Pancer customary law in Pesucen village, Kalipuro sub-district, Banyuwangi sub-district, such as marrying a cousin from a father whose brothers are both male, is a prohibition that has become a rule. However, in Islamic law, it is permissible to marry cousins, and there is no evidence against it. The purpose of this study is to describe the traditional practice of Pancer in marriage and to describe the views of Ulama' Fiqh on the Pancer custom in Pesucen village, Kalipuro district, Banyuwangi district. This study uses a qualitative approach with descriptive exposure. The results show that the Pancer custom in Pesucen village is considered to have violated the rules by not allowing marriage to occur between cousins, even though marriage between cousins ​​is allowed. Adat which usually can be used as a reference for a particular case means that it can also be used as a syar'i argument. However, if it is against the text, it can no longer be used as a reference. Because basically custom is not allowed to justify the haram and it is also not allowed to justify the halal.